Development of good honey index for stingless bee honey based on its comprehensive physicochemical profiling - Abdul Rahman, Muhammad Fahdli (2018)
Honey is the oldest natural and nutritious food that can support human health. Honey is very important in Malaysia as daily supplement food. Recently, the demand for stingless bee honey has increased due to its extraordinary benefits. Unfortunately, the honey naturally has limited production, and there is no strict procedure on how to sell good and authentic honey. Therefore, fake honey is widely sold in the marketplace to fulfil economic needs. This work focused on comprehensive profiling and the development of a good honey index (GHI) for stingless bee honey. The GHI composes three components; 1) the characteristic of honey, 2) the goodness of honey, and 3) the compliance to the Malaysian Standard (MS 2683:2017). Each component was constructed by several sub-components, and the data matrices were validated using statistical tools. 29 honey samples were tested, including 13 that were harvested from local bee farms, and 16 were bought from the local market. Investigation showed that chemical and elemental composition level is significantly different in most honey samples. The parameter for the characterization of comprehensive profiling such sugar and metal profiles was applied with the similarity distance. However, hierarchical cluster analysis (HCA) suggested that some composition patterns followed the bee species. The physicochemical properties of stingless bee honey was analyzed in the goodness of honey component includes metal daily consumption, water activity (aw), antimicrobial activity, total phenolic compound, DPPH and FRAP antioxidant activities. While under the compliance to Malaysian Standard comparisons of sugar; fructose and glucose, sucrose, maltose are made for the requirement of sugar level of stingless bee honey. Factorial analysis was carried out using the Kaiser-Meyer-Olkin (KMO) analysis in three components such as the characteristic of honey, the goodness of honey, and the compliance to Malaysian Standard for stingless bee that resulted in a KMO value of 0.661, 0.735 and 0.614 with all the component with p-value ≤ 0.05. Power analysis was carried out to measure the adequacy of the sample size, resulted in 96.4% of sampling power. The limit for GHI was set at 60, and 90% of raw honey samples passed the index threshold with the highest score of 89 from sample K91. For the commercial honey samples, only 50% passed the GHI threshold. In conclusion, a chemometric analysis of a complex characteristic of stingless bee honey has been demonstrated. Consequently, a newly developed GHI that can be used for the grading system to evaluate and qualify stingless bee honey quality for commercialization.